Sources of financial synchronism: Arbitrage theory and the promise of risk-free profit - Andreas Langenohl (Finance and Society, 2018)
This article argues that the temporality of the financial economy ought to be seen as radically synchronistic. "Synchronism" refers to both an epistemological and practical approach that addresses finance neither with a view to the past nor to the future, but is instead focused on the moment that a financial transaction is settled (i.e., the horizon of trading). From this perspective, the article expands the scope of current social theorizing on financial markets, which is characterized by a preoccupation with the futurity of financial markets and products. It suggests that financial synchronism can be traced back to certain developments in economic theory since the so-called "marginalist revolution", which enabled the transfer of a certain optics informing market theories into financial practices. On these terms, financial synchronism is interpreted as a powerful social imaginary that crucially mediates the way contemporary societies face the contingency of the future.
Keywords: 300; Finance; trading; temporality; synchronism; arbitrage; risk